The Cleft Lip Education with Augmented Reality (CLEAR) VR Phase 2 Trial: A Pilot Randomized Crossover Trial of a Novel Patient Information Leaflet. (February 2023) - Lo, Steven John; Chapman, Paul; Young, David; Drake, David; Devlin, Mark; Russell, Craig
Background: The Cleft Lip Education with Augmented Reality (CLEAR) project centers around the use of augmented reality (AR) in patient leaflets, as a visual means to overcome the "health literacy" gap. This trial followed Virtual Reality (VR CORE) guidelines for VR Phase 2 (Pilot) trials. Methods: Participants included families of children treated for Cleft Lip and Palate at the Royal Hospital for Children, Glasgow. Interventions were AR leaflet or Traditional Leaflet. Objectives were to calculate sample sizes, assess outcome instruments, trial design, and acceptability to patients. Primary outcome measure was Mental Effort Rating Scale, and secondary outcomes were Patient Satisfaction (Visual Analogue Scale), Usefulness Scale for Patient Information Material (USE) scale, and Instructional Materials Motivation Survey (IMMS). Randomization was by block randomization. The trial was single blinded with assessors blinded to group assignment. Results: 12 Participants were randomized, with crossover design permitting analysis of 12 per group. Primary outcome with Mental Effort Rating Scale indicated higher mental effort with Traditional compared to AR Leaflet (4.75 vs 2.00, P = .0003). Secondary outcomes for Satisfaction were Traditional 54.50 versus AR 93.50 ( P = .0001); USE scale 49.42 versus 74.08 ( P = .0011); and IMMS 112.50 versus 161.75 ( P = .0003). Subjective interviews noted overwhelmingly positive patient comments regarding the AR leaflet. Outcome instruments and trial design were acceptable to participants. No harms were recorded. Conclusions: The CLEAR pilot trial provides early evidence of clinical efficacy of AR leaflets in patient education. It is hoped that this will provide a future paradigm shift in the way patient education is delivered.